Fatty Acid Binding Protein 4—A Circulating Protein Associated with Peripheral Arterial Disease in Diabetic Patients - Zamzam, Abdelrahman (J Clin Med, 2020)
Diabetic patients with peripheral arterial disease (PAD) often suffer from poor clinical outcomes such as limb-loss. Fatty acid binding protein 4 (FABP4) is mainly expressed by adipocytes and is known to play a significant role in the development of atherosclerosis. In this study, we sought to investigate whether FABP4 is associated with PAD in patients with type 2 diabetes mellitus (DM). FABP4 plasma levels were studied in 119 diabetic patients with PAD (DM-PAD) and 49 diabetic patients without PAD (DM-noPAD) presenting to St. Michael’s Hospital between October 2017 and September 2018. Levels of FABP4 in DM-PAD patients (23.34 ± 15.27 ng/mL) were found to be over two-fold higher than the levels in DM-noPAD patients (10.3 ± 7.59 ng/mL). Regression analysis demonstrated a significant association between FABP4 levels and DM-PAD after adjusting for age, sex, prior history of coronary arterial disease and white blood cells count (OR, 2.77; 95% CI, 1.81–4.31; p-value = 0.001). Relative to DM-noPAD controls, plasma FABP4 levels in DM-PAD patients were noted to be inversely correlated with the ankle brachial index (ABI; r= −0.374, p-value < 0.001). The diagnostic ability of FABP4 was investigated using receiver operator curves (ROC) and area under the curve (AUC) analysis. FABP4 had an AUC of 0.79, which improved to 0.86 after adjusting for age, sex and prior history of coronary arterial disease. This raises a possibility of utilizing FABP4 as a biomarker for diagnosing PAD in diabetic patients.